PENGARUH CELEBRITY ENDORSEMENT TERHADAP CONGRUENCY DENGAN BRAND PERSONALITY DAN BRAND POSITIONING SEBAGAI VARIABEL INTERVENING PADA PRODUK SEPATU OLAHRAGA NIKE KOBE SERIES - Albert Nathanael Gunawan (Jurnal Strategi Pemasaran, 2016)
This study aimed to analyze the effect of Celebrity Endorsement towards Congruency with considering the effect of Brand Personality and Brand Positioning. This study will be conducted by distributing questionnaires to 100 respondents who have ever made a purchase of the Nike brand sports shoes Kobe Series. Analysis technique used is quantitative analysis technique.